Euglycemic diabetic ketoacidosis following major vascular surgery is a new item on the differential for postoperative acidosis - Clara M. Gomez-Sanchez, MD (Elsevier, 2021)
New pharmacologic advances in the treatment of diabetes include SGLT-2 inhibitors, which have been demonstrated in randomized-controlled clinical trials to reduce overall and cardiac-specific mortality and slow progression of chronic kidney disease. Euglycemic diabetic ketoacidosis is a rare but life-threatening complication associated with the use of SGLT-2 inhibitors. Here we describe a case of severe euglycemic diabetic ketoacidosis after lower extremity bypass in a patient taking an SGLT-2 inhibitor. Awareness of this potential complication is essential as these novel agents are increasingly used in patients with cardiovascular disease.